Raisonner sur l’absence. Prospections géophysiques croisées au prieuré grandmontain d’Époisses à Bretenière (Côte-d’Or) - Marion Foucher; Ronan Steinmann (Bulletin du Centre d’Études Médiévales d’Auxerre)
In 2017, while a reorganisation project of the INRAE’s experimental unit in Époisses-Bretenières (Côte-d’Or) was under study, the former priory belonging to the order of Grandmont has been the object of a research campaign crossing medieval and modern archives, built remains and geophysical surveys. The main purpose aimed the reconstruction of the medieval priory and the different spaces organized around the cloister, starting from the only preserved remains of its chapter house. Finally, the surveys have led to a reflection on the lack of buried structures, considered as the possible sign of a practice rather than of an artefact.